The expanded clinical profile and the efficacy of colchicine therapy in Egyptian children suffering from familial mediterranean fever: a descriptive study - Talaat Hala Salah El-Din; Mohamed Mohamed Farouk; El Rifai Nihal Mohamed; Gomaa Mohamed Ali (BMC, 2012)
Abstract Background Familial Mediterranean fever (FMF) is an autosomal recessive disease characterized by self-limiting recurrent attacks of fever and serosal inflammation, leading to abdominal, thoracic or articular pain. Objective To detect variable clinical presentations and genotypic distribution of different groups of FMF patients and the efficacy of colchicine therapy in treatment of these groups of FMF after one year. Methods A cross-sectional study was conducted on 70 patients already diagnosed with FMF and following-up at the Rheumatology Clinic, Children's Hospital - Cairo University. Diagnosis of FMF was determined according to Tel Hashomer criteria for FMF. All patients were subjected to a questionnaire including detailed history with emphasis on clinical manifestations and colchicine dose to control attacks. Mutational analysis was performed for all study subjects covering 12 mutations in the MEFV gene: E148Q, P369S, F479L, M680I (G/C), M680I (G/A), I692del, M694V, M694I, K695R, V726A, A744S and R761H. Response to colchicine treatment was evaluated as complete, incomplete and unresponsive. Results Out of the 70 patients- 40 males and 30 females- fever was the most common presenting feature, followed by abdominal pain, and arthritis; documented in 95.7%, 94.3%, and 77.1% of cases respectively. Mutational analysis detected gene mutation on both alleles in 20 patients (homozygotes), on only 1 allele in 40 patients (heterozygotes), and on none of the alleles (uncharacterized cases). Mild to moderate disease severity score (according to Tel Hashomer key to severity score) was detected in a significant proportion of heterozygotes and the uncharacterized group than the homozygotes. All patients received colchicine therapy; 22.9% of them showed complete response, 74.3% showed incomplete response and 2.9% showed no response to therapy. The colchicine dose needed to control attacks was significantly lower in heterozygotes than the homozygotes(P=0.04). Also patients' response to colchicine therapy was significantly better in the heterozygous group(P=0.023). Conclusion Fever, abdominal pain and arthritis are the most common presenting features for homozygous, Heterozygous and uncharacterized patients. E148Q, V726A, and M680I were the most common mutations detected in the heterozygous group. Homozygosity were found for M680I, M694V, and M694I mutations in 13 patients (65% of homozygotes). Heterozygotes presenting with severe phenotype should be further analyzed for less common second MEFV mutation using gene sequencing. The colchicine dose required to control the attacks was significantly lower and patients' response to colchicine therapy was significantly better in the heterozygous group than homozygous group.